2003
DOI: 10.1097/00000542-200305000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Doppler Assessment of Pulmonary Capillary Wedge Pressure in Surgical Patients with Postoperative Circulatory Shock and Acute Lung Injury

Abstract: In patients with postoperative circulatory shock and acute lung injury, transesophageal echocardiography estimates noninvasively PCWP. However, echocardiographic estimation of PCWP may not be accurate enough for adjusting therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 40 publications
1
52
0
1
Order By: Relevance
“…The protocol was approved by the local Ethical Committee ( Comité de Protection des Personnes , Ile de France VI, Groupe Hospitalier Pitié-Salpêtrière, Paris, France, session nº18/2011) who considered the study an integral part of care provided to patients with ARDS and septic shock and waived the need for patients to give written informed consent. In our ICU, such patients are routinely monitored using a PiCCO or a fiber optic Swan-Ganz catheter [14-16] and transthoracic lung ultrasound is a common procedure to assess changes in lung aeration [6,7,17]. Thirty-two mechanically ventilated patients were included within 48 h following onset of septic shock and ARDS, defined according to referent recommendations [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was approved by the local Ethical Committee ( Comité de Protection des Personnes , Ile de France VI, Groupe Hospitalier Pitié-Salpêtrière, Paris, France, session nº18/2011) who considered the study an integral part of care provided to patients with ARDS and septic shock and waived the need for patients to give written informed consent. In our ICU, such patients are routinely monitored using a PiCCO or a fiber optic Swan-Ganz catheter [14-16] and transthoracic lung ultrasound is a common procedure to assess changes in lung aeration [6,7,17]. Thirty-two mechanically ventilated patients were included within 48 h following onset of septic shock and ARDS, defined according to referent recommendations [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…However, "preload independence" of early diastolic mitral annulus motion (E′) is still debatable, and the effects of acute alterations in preload, afterload, and contractility on E′ and their related influence on E/E′ have not been proved [58,61]. Recent studies performed in critical care patients have tried to correlate E/E′ and PAOP with variable success [60][61][62][63][64]. Echocardiographic guidelines suggested that an E/ E′ ratio less than 8 accurately identified patients with a normal pressure and a ratio greater than 15 those with an elevated PAOP.…”
Section: Limitations Of the Falls Protocol And Cardiac Function Analymentioning
confidence: 99%
“…In patients with intermediate values (N8 and b15), PAOP may vary widely, and the other Doppler flow methods can be used [65]. Finally, TTE may provide simple logistics for grading LV diastolic dysfunction by using pulsed and tissue Doppler at the mitral valve and at the mitral annulus, facilitating thus cardiac function analysis in various cardiodynamic scenarios [60][61][62][63][64][65]. Notably, B predominance in LU does not always reflect elevated PAOP in shock states (Fig.…”
Section: Limitations Of the Falls Protocol And Cardiac Function Analymentioning
confidence: 99%
“…Some studies have also established that variations in E/E' accurately track changes in LV diastolic pressures under (un)loading therapy [48,55,56]. Clinical studies that found significant correlation between the spectral E/E' ratio and invasively determined pulmonary capillary wedge pressure or mean LV diastolic pressure in the setting of preserved LV systolic function are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%